Analysis of degraded casework DNA by redesigning a mini Y-STR multiplex. (December 2017) - Gu, Y.; Zhang, Z.; Wu, D.; Zha, L.; Gao, T.; Yun, L.
Abstract: As partial genetic profile from degraded DNA samples of a case limiting the application of Y-STRs in forensic sciences, a new multiplex mini Y-STR typing was developed to obtain more useful information and complement current commercially available multiplex kits. The multiplex mini Y-STR amplification including three Y-STR loci (DYS385a/b, DYS389 II, and DYS392) was performed to generate amplicons smaller than those of PowerPlex ® Y system over 140 bp by redesigning primers. Allelic ladders for three mini Y-STR loci were created using a dilution of allelic ladders from the PowerPlex ® Y system. A sensitivity test using serially diluted standard 9948 male DNA showed that three mini Y-STR loci were reliable at template concentrations as low as 0.25 ng. By comparing of the multiplex mini Y-STR amplification and PowerPlex ® Y system with referenced DNA samples, the results indicated stable concordance in genotyping. And then the successful analysis for the degraded DNA samples from the forensic case produced complete genetic profiles with these three loci. So the multiplex mini Y-STR typing combining the aforementioned commercially available kit increased chance of gaining of 16 Y-STR loci profiles within some core loci in Y Chromosome Haplotype Reference Database from forensic casework sample. It is an alternative strategy for recovering locus-specific information from degraded to redesign the suitable mini Y-STR complement besides new commercial Y-STR kits.